Pengaruh Kompensasi dan Disiplin Kerja terhadap Kinerja Kurir Shopee Express Ciamis - Amartya Ainun Qalbia; Arga Sutrisna; Suci Putri Lestari (CV. Ulil Albab Corp, 2022)
This study aims to determine the effect simultaneously and partially between Compensation and Work Discipline on the Performance of the Ciamis Shopee Express Courier. The research method used is a survey method with a quantitative approach. The sampling technique used the saturated sample method with a total sample of 35 peoples. Data collection techniques using online questionnaires. The data used is primary data. The analytical tool used in this study is multiple regression using SPSS 26. The results show that compensation and work discipline have a significant effect on performance simultaneously. Partially, compensation has a significant effect on performance. Partially, work discipline has a significant effect on performance.